An institutional order for a globalizing world economy - Horst Siebert (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
The paper discusses the most important elements of an institutional order for a globalizing world economy. Rules for the exchange of goods, for factor movements, for the monetary domain and for the allocation of the environment are distinguished. It is analyzed in which direction these rules should be developed. The interdependence of the institutional order for these different areas is discussed.
Keywords: F02; 330; Weltwirtschaftsordnung; WTO-Regeln; Globalisierung; Welt